Enterprise Architecture Design Using the Togaf Architecture Development Method (Togaf-Adm) Framework at The Library of SMAN 22 Jakarta - Rifio Riztriano (Jurnal Komputer, Informasi dan Teknologi, 2025)
This research aims to design an enterprise architecture blueprint for the SMAN 22 Jakarta Library to improve service quality and minimize operational problems caused by the current manual system, such as frequent data loss. The Library, a key division in the education sector, currently executes functions like member registration, book borrowing, and returns, using traditional methods. The enterprise architecture design is necessary to align business strategies and information technology to support future development. The methodology used is the TOGAF Architecture Development Method (TOGAF-ADM) framework. This research specifically utilizes six phases of TOGAF-ADM: Preliminary Phase, Requirements Management, Phase A (Architecture Vision), Phase B (Business Architecture), Phase C (Information System Architecture), and Phase D (Technology Architecture). Each phase is used to produce a comprehensive architectural blueprint. The results of this study are proposed architectural blueprints for the SMAN 22 Jakarta Library, encompassing the current and target architectures for Business, Data, Application, and Technology domains. These blueprints offer a clear visualization of the alignment between business functions and the required Information Technology infrastructure and systems. In conclusion, the designed enterprise architecture, particularly the proposed personnel information system function, can serve as a valuable reference and foundation for future business development and information technology strategic planning at the SMAN 22 Jakarta Library.